СПЕКТРАЛЬНІ ХАРАКТЕРИСТИКИ ПЕРВИННИХ ВИМІРЮВАЛЬНИХ КАНАЛІВ СТРУМУ ВИСОКОВОЛЬТНИХ ЕЛЕКТРИЧНИХ ПІДСТАНЦІЙ - Паньків, В.І.; Танкевич, Є.М. (Інститут електродинаміки Національної академії наук України, 2018)
The electromagnetic processes in the current transformer of the high-voltage primary measuring current channel in the transient conditions of the power system are calculated and the spectral analysis of the current channel is conducted using the discrete Fourier transform. It has been suggested and recommended to use the spectral analysis of current channel to solve a number of problems of electric power engineering. References 6, figures 3.